Evaluation of the Cardiopulmonary Resuscitation Expertise of the Demonstrators of Dental College - Farheen Malik, Mahnoor Munir, Muhammad Mutahir Mehdi, Muhammad Waheed Tahir, Nida Badar, Rabia Mahmood (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Cardiac arrest thought as topmost cause of a death in various regions of globe. Cardio-pulmonary arrest (CPA) is unexpected and swift halt/end in the patients breathing or/and circulation because of numerous causes. CPR incorporates comprehensive hard work as well as those practices for a recovering of any person who is facing cardiac failure Aim: To see as well as examine medical skills of demonstrator’s as per latest CPR regulatory principles & to pinpoint those precautionary measures Study design: Cross-sectional study Place and duration of study: This study of 3 months duration was carried on demonstrators of Multan dental college, Multan. Methodology: 40 demonstrators willingly took part in study. Simple random sampling technique was utilized in order to collect the data. Well-structured Performa was consumed. Informed consent was also sign up from contestants. Results: Men were sixteen while ladies were twenty four. 24(60%) applicants failed in initial assessment, 28(70%) participants reported failure due to compression rate error, 22(55%) participants were failed due to ventilation rate error and 12(30%) participants failed due to incorrect hand position Conclusion: The level of both knowledge and training about medical related emergencies of demonstrators is less than desirable level. Hence, it is needed to set accurate strategies and plans in order to fortify the known areas of weakness. Keywords: Cardio-pulmonary arrest, Cardiopulmonary resuscitation, guiding principles, Medical emergencies